Endoscopic eyebrow-eyelid sparing orbital exentration in mucormycosis - Munjal, Manish; Singh, Gagandeep; Rishi, Porshia; Singh, Harjinder; Munjal, Shubam; Talwar, Shivam; Sharma, Salony; Chugh, Tej Mehar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
The intra-vascular invasion progressively halts the blood flow in the arterial distributaries and the venous tributaries and finally a “blue black”, wet gangrenous region is noted. Later the underlying bone too becomes fragile and crumbles off. Removal of necrotic debris remains the main stay of management. Removal of foci of infection, the orbital soft tissues utilizing high resolution endoscopic modality is elaborated upon.